2022
DOI: 10.3389/fmats.2022.862796
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Mapping Using Nanocomposite-Enhanced Foam and Machine Learning

Abstract: Pressure mapping has garnered considerable interest in the healthcare and robotic industries. Low-cost and large-area compliant devices, as well as fast and effective computational algorithms, have been proposed in the last few years to facilitate distributed pressure sensing. One approach is to use electrical impedance tomography (EIT) to reconstruct the contact pressure distribution of piezoresistive materials. While tremendous success has been demonstrated, conventional algorithms may be unsuitable for real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Then, two different synthetic datasets were generated according the procedure explained in Section “Preparation of the training dataset.” The first dataset was built by considering single and multiple polygonal defects, with random shapes and positions in the region of interest, where conductivity was reduced by a random factor (0%–100%). More details about data generation for polygonal defects can be found in Quqa et al 55 The second dataset was generated considering randomly distributed line-shaped regions with zero conductivity in the sensing surface. Specifically, a crack was modeled as a random number of connected segments (between 1 and 10) with random length (max 2 cm) and inclination.…”
Section: Experimental Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, two different synthetic datasets were generated according the procedure explained in Section “Preparation of the training dataset.” The first dataset was built by considering single and multiple polygonal defects, with random shapes and positions in the region of interest, where conductivity was reduced by a random factor (0%–100%). More details about data generation for polygonal defects can be found in Quqa et al 55 The second dataset was generated considering randomly distributed line-shaped regions with zero conductivity in the sensing surface. Specifically, a crack was modeled as a random number of connected segments (between 1 and 10) with random length (max 2 cm) and inclination.…”
Section: Experimental Investigationmentioning
confidence: 99%
“…EIT has also shown to be effective in detecting strain states. 55 Embedded cracks near the free surface (e.g., delamination) or small cracks due to a tensile state may not involve disconnections in the sensing film. However, in general, they generate a variation in the surface strain, which changes the conductivity of the sensing film.…”
Section: Experimental Investigationmentioning
confidence: 99%
“…This strategy was proposed in previous studies (Quqa et al., 2022; Quqa et al, 2023) and will be used here to represent the reference performance of a DNN‐based method to solve the inverse ERT problem. This DNN will be referred to as “preliminary” DNN hereafter, as it is trained on synthetic data alone.…”
Section: Deep Learning For Distributed Sensingmentioning
confidence: 99%
“…Previous studies showed that, in some cases, synthetic data alone could be enough to train neural networks for the identification of conductivity changes due to damage or strain variations when the sensing body is originally undamaged (Quqa et al., 2022). Nevertheless, while early damage might be identified with good accuracy (Quqa et al, 2023), the performance of neural networks typically degrades with damage severity (L. Chen, Gallet, et al., 2022; Hallaji et al., 2014; Seppänen et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, DL also has good migration ability and can be used to solve the problem of improving the resolution of complex tongue tactile imaging. Deep neural networks, such as deconvolution neural networks (DNNs), have shown great potential in improving the resolution of tactile perception imaging (Funabashi et al, 2022; Huang et al, 2020; Kim et al, 2021; Quqa et al, 2022). It can efficiently transform the distributed information of sparse original pressure contacts into high‐resolution tactile image close to tongue tactile perception.…”
Section: Introductionmentioning
confidence: 99%